Badges: How to use?: Training teachers trought a MOOC - Araújo, Inês (2018)
In the scope of the school activities of the GamiLearning project, badges were issued to students, aiming to engage them in the online community created in the SAPO Campus platform. Analyzing the use of badges in the platform, it was possible to identify that only a few communities actually used the badges tool. In order to promote the use of Badges by the members of these schools a MOOC was designed and implemented. The MOOC was named “Badges: how to use?” and started on the 20th of April of 2017. This paper presents the assumptions underlying the creation of this MOOC, explaining how it was organized. It characterizes its participants and remarks are given on how to continue working with the participants through a community of practice about badges.